Title: Traction Table Effect on Lumbar Spine by Using The Finite Element Method and Modeling - Hekmat Farajpour; Nima Jamshidi; Asghar Golmohammadi (Vesnu Publications, 2015)
Introduction: Low back pain is one of the most important problem that exists worldwide. About 80 to 90% of low back pains are acute. Herniated disc between L4-L5 vertebrae and disc rupture are the main reasons for this type of low back pain. Treatment for this type of back pain is stretching the spine with traction table. Traction table helps low back pain treatment by increasing the height of discs and putting distance between facet joints.  Materials and Methods: In this study, 3D model of the lumbar spine of a 31-year-old and 83 kg female was made by using CT scan images and MIMICS10.01 software. This model was imported in Abaqus6.11 software for analysis. In this software, materials properties of spine segments were modeled and traction table loading was applied to the model. Then results were compared with previous experimental studies.The goal of this study was presented a method to evaluated the traction table effect on spine and this method presented by 3D modeling and using finite element method. Results:After loading was applied in Abaqus software, the displacement of discs between L4-L5 and L3-L4 vertebrae was obtained 2.59 mm and 1.81mm, respectively. The results were validated by comparing with previous experimental studies, in which discs displacement were analyzed by using MRI and CT scan images before and after traction. Conclusion: Traction table is effective on discs displacement and reducing the back pain. Key Words: Traction Table, Modeling, Low Back Pain, Finite Element